Ensefalitis Herves Simplex pada Anak - Hidayah, Nurul; Muhyi, Ruslan (Fakultas Kedokteran Universitas Lambung Mangkurat, 2014)
Abstract: Herpes simplex virus is a cause of encephalitis in human whose high fatality rate. Herpes Simplex Encephalitis (EHS) can occured in all range of ages without sex predilection with case incidence about 1 in 250.000-500.000 populatation/years. About 40% patients hospitalized in coma state. Coma is a very poor prognostic factors, because patients with coma often died or recovered with severe sequelae. Mortality usually occured in first 2 weeks. In children, this disease has an unspesified clinical manifestation therefore in order to diagnose EHS, a strong clinical suspicion is needeed. In a simple way, we can suspect a children with EHS possibility if a child suffer from febrile, seizure (especially focal seizure) dan other focal neurological symptoms such as hemiparesis or disphasia with progrressive lost of consciousness.Key words: encephalitis, herpes simplex, child Abstrak: Virus Herpes simplex adalah penyebab ensefalitis pada manusia yang seringkali berakibat fatal. Ensefalitis herpes simplex dapat menyerang semua umur, tanpa predileksi jenis kelamin. Angka kejadian adalah 1 dalam 250.000-500.000 populasi per tahun. Empat puluh persen pasien datang di rumah sakit dalam keadaan koma. Koma merupakan faktor prognosis yang sangat buruk, pasien yang mengalami koma seringkali meninggal atau sembuh dengan gejala sisa yang berat. Kematian biasanya terjadi dalam 2 minggu pertama. Manifestasi klinis sangat tidak spesifik terutama pada anak dan diagnosis EHS sangat memerlukan kecurigaan klinis yang kuat. Secara praktis, fikirkan kemungkinan EHS bila menjumpai seorang anak dengan demam, kejang terutama kejang fokal dan gejala neurologis fokal lain seperti hemiparesis atau disfasia dengan penurunan kesadaran yang progresif. Kata-kata kunci : ensefalitis, herpes simplex, anak Ensefalitis Herves Simplex pada Anak